Robust state estimation of power systems based on equivalent measurement technique - Sermsak Uatrongjit (2018)
© 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc. The paper investigates the application of the equivalent measurement technique to the robust state estimation (SE) of power systems. In contrast to the weighted least square-based SE method, the objective functions of the robust SE tend to suppress the influence of bad data contained in the measurement set during the estimation process. So there is no need to perform bad data elimination. In the proposed approach, the collected measured data, such as the power flowing through the transmission line, the injection power, and bus voltage magnitude, are converted into equivalent measurements as either current or voltage phasor quantities. Also the state variables are expressed in rectangular coordinates. This enables the relationship between the state variables and the measurements to be described by the linear measurement function and its Jacobian matrix is computed only once during the iterative solution computation. Some testing results of the standard IEEE test systems indicate that the proposed approach uses less computation time and still provides similar accuracy compared to the conventional SE. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.